Perceived issue in the possible implementation of RFID tagging on FTMSK student card / Caroline Annie Jerry - Jerry, Caroline Annie (2005)
RFID is starting to become an integral part of the information technology (IT) solution in organizations. It will become the future successor of barcode technology as it expands the barcode fimctionality. With much benefit that it offers to organizations, it is still a wonder that many especially the public (consumer) have doubts on the implementation of radio frequency identification (RFID) technology in their daily live. With the security and privacy issues being brought out, many fears that with the technology it would enable unwanted parties to gain access to the information kept in the tag and used the information against them. This study determines the possibility of RFID technology to be deployed in information technology and science quantitative faculty (FTMSK) and also in what ways it can be deployed. Apart from that, this study attempts to clarify the main privacy issue that may arise due to the deployment and developing guideline that can be used in the deployment of RFED systems.